2008
DOI: 10.1016/j.tripleo.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Building biofilms in vital host tissues: a survival strategy of Actinomyces radicidentis

Abstract: OBJECTIVE: To investigate the ability of Actinomyces radicidentis to survive and establish in soft connective tissue that grew into subcutaneously implanted tissue cages in Sprague-Dawley rats. STUDY DESIGN: Known concentrations of A. radicidentis suspension, grown on blood agar and broth cultures, were inoculated into tissue cages in rats. The cage contents were retrieved after 7, 14, and 28 days for culturing and correlative light and transmission electron microscopy. RESULTS: Cell suspensions harvested from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…Actinomyces radicidentis is known to form biofilms, in which bacteria seem to be embedded in the extracellular matrix and exhibit antiphagocytic activity against rat neutrophils (Nair et al . ). Actinomyces meyeri , the cause of various actinomycosis or abscess lesions (Apothéloz & Regamey , Liaudet et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Actinomyces radicidentis is known to form biofilms, in which bacteria seem to be embedded in the extracellular matrix and exhibit antiphagocytic activity against rat neutrophils (Nair et al . ). Actinomyces meyeri , the cause of various actinomycosis or abscess lesions (Apothéloz & Regamey , Liaudet et al .…”
Section: Discussionmentioning
confidence: 97%
“…A recent study demonstrated the capacity of A. israelii to produce EPSs and to form biofilm in vitro on copper surfaces of intrauterine contraceptive devices immersed in a simulated uterine fluid under anaerobic conditions (Carrillo et al 2010). Actinomyces radicidentis is known to form biofilms, in which bacteria seem to be embedded in the extracellular matrix and exhibit antiphagocytic activity against rat neutrophils (Nair et al 2008). Actinomyces meyeri, the cause of various actinomycosis or abscess lesions (Apothéloz & Regamey 1996, Liaudet et al 1996, was also found in periapical lesions refractory to endodontic therapy (Sunde et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Simple culture of Actinomyces in BAL, as with sputum, is inappropriate for the diagnosis of pulmonary actinomycosis, except for patients with cavitation, as it may represent colonization 45. In patients with pulmonary actinomycosis associated with pleural effusion, it is of importance to note that Actinomyces almost never grow from pleural effusion samples.…”
Section: Clinical Features Of Actinomycosismentioning
confidence: 99%
“…A link between CF and the VBNC form was noticed in a variety of microorganisms, for example, Actinomyces radicidentis [32], V. vulnificus [33], V. cholera [34], Mycobacterium smegmatis [35] and Salmonella typhimurium [36]. Association of CF with the VBNC state of C. jejuni would help to explain the incidences of infections by Campylobacter with no discernable environmental source [37].…”
Section: Properties Of Coccoid Formsmentioning
confidence: 99%